Enhancing Culinary Msmes Performance Through TQM and Lean Production - Sembiring, Kornelius Alfredo; Nuraini Desty Nurmasari (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to identify the effects of Total Quality Management (TQM) and lean production on the performance of culinary micro, small, and medium-sized enterprises (MSMEs) in Malang City. Design/Methodology/Approach – This study employs a quantitative explanatory research design. Data were collected through questionnaires and analyzed using multiple linear regression to examine the effects of TQM and lean production on the performance of culinary MSMEs. Findings – The results indicate that both Total Quality Management (TQM) and lean production have positive and significant effects on the performance of culinary MSMEs in Malang City, supporting both research hypotheses. These findings suggest that the implementation of effective operational strategies can improve the competitiveness and sustainability of culinary MSMEs. Originality/Value This research provides value by empirically examining the roles of TQM and lean production in improving MSME performance within the culinary sector, offering evidence-based insights to guide operational strengthening and long-term sustainability.